PENYULUHAN PENINGKATAN PENGETAHUAN PADA ORANG TUA PENDERITA STUNTING PADA BALITA 0-59 BULAN DI KECAMATAN PANGA, ACEH JAYA - Lensoni; Rani, Siti (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2021)
Stunting is a condition characterized by shorter height compared to individuals of the same age group, which affects physical performance as well as mental and intellectual functions. Stunted toddlers often lag behind in various aspects of development, including fine motor skills, gross motor skills, language, and personal-social skills. This study aims to examine the relationship between stunting and the development of children aged 0-59 months in the working area of Panga Health Center, Aceh Jaya. The research design employed in this study was a pre-experimental design known as the One Group pretest-posttest design. The sampling technique used was total sampling, and the obtained data were analyzed using the Paired Simple T-Test with a significance level of 0.05. The study sample consisted of 37 respondents from the Panga Health Center working area, selected using total sampling. The research findings indicate that prior to counseling, most parents had moderate knowledge (91.9%), while after receiving counseling, a majority of parents had a fairly high level of knowledge (100%). The data were further analyzed using the Peired Simple T-Test correlation test, yielding a p-value of 0.00 < 0.05, indicating the rejection of the null hypothesis (Ho) and thus establishing a relationship between stunting incidence and its development in Panga District, Aceh Jaya. Specifically, personal-social skills, fine motor skills, language, and gross motor skills were found to be partially associated with stunting. Additionally, the bivariate analysis revealed a p-value of 0.00, demonstrating an influential effect of counseling on parents' knowledge concerning the risks of stunting in Panga District, Aceh Jaya Regency.